Rapid progressive seeding of a community acquired pathogen in an immune-competent host: end organ damage from head to bone - Daisy Torres-Miranda; Farah Al-Saffar; Saif Ibrahim; Stephanie Diaz-Font (MDPI AG, 2015)
Methicillin-sensitive Staphylococcus aureus (MSSA) meningitis is a rare disease when not related to neurosurgery: there are only few reported cases in the literature to date. We describe a case that highlights not only meningeal but also diffuse and rapidly progressive systemic involvement with multi-organ failure. A 64-year-old male presented to our hospital with a chief complaint of acute worsening of his usual chronic lower back pain, progressive weakness in lower extremities and subjective fevers at home. Hospital course demonstrated MSSA bacteremia, of questionable source, that resulted in endocarditis affecting right and left heart in a patient with no history of intravenous drug use. The case was complicated by septic emboli to systemic circulation involving the kidneys, vertebral spine, lungs and brain with consequent meningitis and stroke, even when treated empirically with vancomycin and then switched to nafcillin as indicated. Even though MSSA infections are well known, there are very few case reports describing such an acute-simultaneous-manifestation of multi-end-organ failure, including meningitis and stroke. Our case, also presented with an uncommon manifestation of persistent infection dissemination despite adequate antibiotic treatment.